1997
DOI: 10.1161/01.cir.96.11.3867
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Percutaneous Treatment of Unprotected Left Main Coronary Stenoses

Abstract: This Article Abstract Google ScholarArticles by Ellis, S. G. Articles by Erbel, R. Search for Related Content PubMed PubMed CitationArticles by Ellis, S. G. Articles by Erbel, R. Pubmed/NCBI databases Medline Plus Health Information AngioplastyBackground Coronary artery bypass surgery (CABG) has been considered the therapy of choice for patients with unprotected left main (ULMT) coronary stenoses. Selected single-center reports suggest that the results of percutaneous intervention may now approach those of CAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(105 citation statements)
references
References 11 publications
3
100
0
2
Order By: Relevance
“…With increasing operator experience, refinement in technology, and the availability of improved stent designs, percutaneous coronary intervention (PCI) is now considered the treatment of choice for many high-risk subgroups in whom it was previously contraindicated [1][2][3]. In 2002 an estimated 657,000 PCI procedures were performed on 640,000 patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing operator experience, refinement in technology, and the availability of improved stent designs, percutaneous coronary intervention (PCI) is now considered the treatment of choice for many high-risk subgroups in whom it was previously contraindicated [1][2][3]. In 2002 an estimated 657,000 PCI procedures were performed on 640,000 patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Some studies have demonstrated that stenting of the ULM is feasible and appears to be a promising strategy in selected patients. [3][4][5][6][7][8] Recently, use of a drug-eluting stent (DES), either a sirolimus-eluting stent (SES; Cypher, Cordis, Johnson and Johnson Co) or a paclitaxel-eluting stent (PES; Taxus, Boston Scientific), has been associated with a low restenosis rate. 9 -13 A single-center observational study recently reported encouraging results with the treatment of left main stenosis, either protected or unprotected, with SES.…”
mentioning
confidence: 99%
“…9 However, advances in intervention techniques and the use of DES are providing encouraging results in the treatment of LMCA stenosis. 10 In fact, DES have emerged as the favored percutaneous treatment modality for LMCA stenosis because of significant reductions in restenosis and TLR rates 11 as shown by a number of registries and nonrandomized studies that have demonstrated the effectiveness of DES for LMCA stenosis; 3 -5,12,13 however, there has been scant data available on long-term clinical follow-up in LMCA lesions treated with DES.…”
Section: Discussionmentioning
confidence: 99%